Evaluation of enzymatic and non-enzymatic antioxidant potential of sprouted indigenous legumes from Pakistan - Ambreen Naz; Kashif Razzaq; Nighat Raza; Muzzamal Hussain; Ahmed Mujtaba; Muhammad Inam Afzal; Muhammad Umer; Amnah Mohammed Alsuhaibani; Amal Hassan Al-Shawi; Maryam Umar; Zarina Mushtaq; Muhammad Imran; et al. (International Journal of Food Properties, 2023)
Germination of seeds is a complex process linked to various molecular and biochemical changes that increase the nutritional value. This research has studied the impact of germination on the enzymatic and non-enzymatic antioxidant activities of five domestic staple legumes from Pakistan: chickpea, mung bean, soybean, lentil, and peanut. The maximum moisture content was recorded for chickpea, i.e., 11.7 ± 0.05 g 100 g−1 followed by lentil, soybean, peanut, and mung bean as 9.65 ± 0.02, 8.07 ± 0.01, 7.6 ± 0.01, and 7.31 ± 0.01 g 100 g−1, respectively. The overall augmentation in catalase activity during germination (days 1 to 4) was maximum for lentils, i.e., 76.22%, and ascorbate peroxidase activity for peanuts, i.e., 62.09%. The soybean showed a clear difference from the 1st to 4th days of germination for peroxide activity among all selected legumes with a 37.29% increase. A maximum change in superoxide dismutase was noticed in mung bean. The mung bean also had the highest variation in total flavonoid contents, while total phenolic contents were higher in the chickpea. The radical scavenging activity varied higher in peanuts, while the ascorbic acid content was maximum for soybeans. Among all selected legumes, non-germinated chickpeas showed a lower DPPH value, i.e., 1.15 ± 0.03%, whereas the highest DPPH value was observed in lentils (69.84 ± 0.05%). Thus, the incorporation of ready-to-eat (RTE) germinated legumes with high antioxidant activity would be a contemporary addition to the everyday meal.